A Conjugate-heat-transfer Immersed-boundary Method for Turbine Cooling. (December 2015) - De Marinis, D.; de Tullio, M.D.; Napolitano, M.; Pascazio, G.
Abstract: The first high pressure stage of a modern gas turbine operates at very high temperatures that require complex blade-cooling systems to guarantee high performance and efficiency of the gas turbine while maintaining a very low level of energy losses, though using compressed air for cooling. An accurate and efficient conjugate heat transfer (CHT) solver is thus necessary to compute the flow and temperature fields of the air within the cooling channels and of the gas around the blades—by means of the Navier—Stokes and energy equations—as well as the blade temperature field, by means of the heat conduction equation. Due to the very high geometrical complexity of the cooling channels within the blades, generating a body fitted mesh for the three domains—air, gas and blade—is extremely difficult and time consuming. Nevertheless, many turbine blade-cooling simulations have been performed with success, though at large computational cost, see, e.g., [1] . A promising alternative approach is provided by the Immersed Boundary (IB) method, which discretizes both the solid and fluid fields by means of a single Cartesian grid, thus reducing the grid generation process to a relatively simple and quick task—an interesting review of the IB method and its application is provided in[2] . The CFD group at the Department of Mechanics, Mathematics and Management of the Polytechnic of Bari has chosen such an approach, by first developing and improving an accurate and efficient IB method for the compressible Navier—Stokes equations[3, 4], and later extending it with success to solve CHT problems[5] . At present, these works are limited to two-dimensional serial calculations. The aim of this work is to extend the two-dimensional IB solver to three-dimensions, using a new IB least-squares reconstruction, an advanced data structure and a parallel solver, so as to obtain a computational tool capable of computing very complex CHT problems within reasonable computational times.